STARSP - THE COMPLEX OF PROGRAMS FOR ANALYSIS OF THE SPECTRA OF NORMAL STARS. - Tsymbal, V. V. (Одеські астрономічні публікації, 2017)
STARSP is the first version of analogs of part to CCP7 project. This system allows to make all parts of proceeding and interpretation of stellar spectra in the LTE approach. System works at the IBM/PC-AT computers and may be useful for professionals and students.